A longitudinal network analysis of research trends and policy implications: southernmost of Thailand case study - Rumdon, Komgrit; Longha, Kamonthip; Kaewsuwan, Nawapon; Matcha, Wannisa (International Journal of Electrical and Computer Engineering (IJECE), 2025)
The government funds research projects to address problems, advance knowledge, and support national development. Data repositories are often used to store this research information; however, such information is not optimally used when making the decision. This is particularly important, especially in the areas that require extensive effort and budget allocation to drive development, such as the southernmost provinces of Thailand. This area has been in a violent situation for more than twenty years, leading to poor education, economic challenges, and many more. This study aims to analyze the trends in research topics on these provinces over 30 years (1982–2020) using epistemic network analysis (ENA) on data from the Southern Border Provinces Research Database (SOREDA). Key findings showed a prolonged focus on “education” and “Islamic studies,” reflecting steady government support but raising concerns about its effectiveness. Another important point was that conflict management research arose in response to the surge in violence in 2004 and prolonged existing. The current trending research focused on local–based capital and how it is used to drive society and the economy, such as through tourism. These highlight evolving priorities in addressing the region's challenges and opportunities.